2008
DOI: 10.1111/j.1469-8986.2007.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Event related potentials to emotional adjectives during reading

Abstract: We investigated to what extent emotional connotation influences cortical potentials during reading. To this end, event-related potentials (ERPs) were recorded during reading of high arousal pleasant and unpleasant and low arousal neutral adjectives that were presented at rates of 1 Hz and 3 Hz. Enhanced processing of both pleasant and unpleasant emotional compared to neutral adjectives was first reflected in an amplified early posterior negativity (EPN) starting from 200 ms after word onset. Later potentials (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

62
366
10
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 405 publications
(444 citation statements)
references
References 79 publications
62
366
10
6
Order By: Relevance
“…Positive, negative, and neutral words were presented randomly in a LMT while brain electrophysiological responses were recorded. We found the EPN to be consistently enhanced to emotionally valent (positive and negative) as compared to neutral words, replicating previous results of native language research (Herbert et al, 2008;Kissler et al, 2009;Scott et al, 2009). Importantly, this valence effect showed a bilateral occipito-temporal negativity, which is the typical scalp distribution of the EPN (e.g., Schupp et al, 2003).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Positive, negative, and neutral words were presented randomly in a LMT while brain electrophysiological responses were recorded. We found the EPN to be consistently enhanced to emotionally valent (positive and negative) as compared to neutral words, replicating previous results of native language research (Herbert et al, 2008;Kissler et al, 2009;Scott et al, 2009). Importantly, this valence effect showed a bilateral occipito-temporal negativity, which is the typical scalp distribution of the EPN (e.g., Schupp et al, 2003).…”
Section: Discussionsupporting
confidence: 79%
“…Importantly, this valence effect showed a bilateral occipito-temporal negativity, which is the typical scalp distribution of the EPN (e.g., Schupp et al, 2003). However, the EPN emotion effect in the present study was observed slightly later than emotion effects recently reported by others (Herbert et al, 2008;Kissler et al, 2007).…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations